PERTUSSIS - INFECTION NOT UNDER COMPLETE CONTROL - V. K. Tatochenko ("Paediatrician" Publishers LLC, 2014)
The article covers the problem of pertussis infection in children of various age groups and causes of high prevalence of this infection in the Russian Federation. According to the author's opinion the main factors of such a bad situation with this disease are insufficient registration of the cases, increasing amount of parents' rejections of vaccination with DTP-vaccine, gradual fading of the post-vaccinal immunity and low level of children defense before school, as well as difficulties in diagnostics and atypical clinical course of the disease in adolescents and adults. The issues of modern views on variability of infectious agents, comparative efficacy and immunogenicity of whole cell and acellular vaccines and international experience in usage of acellular DTP-vaccines are reviewed with a special attention. Increasing of the vaccination coverage (due to the switch to the less reactogenic aDTP-vaccines), introduction of booster dosages among younger school children and adolescents, vaccination of pregnant women and cocooning strategy in order to protect newborns and infants under 6 months old can be possible ways to improve epidemiologic situation and control of pertussis infection.